A Rare Case of Post-Partum Hemorrhage with Refractory Thrombotic Microangiopathy, and Hepatic Infarction: A Diagnostic Dilemma with High Mortality - Naved Yousuf Hasan; Asiah Salem Rugaan; Noha Ahmed Mohamed Ali; Masood Iqbal (Gynecology Obstetrics & Reproductive Medicine)
We are presenting a very rare and unique case of postpartum hemorrhage with excessive blood loss requiring 6 units of packed red cells, 2 units of single donor platelet transfusions, 4 fresh frozen plasmas, and 4 cryoprecipitates. The patient developed a life-threatening spectrum of thrombotic microangiopathy which is known to result in pregnancy from eclampsia, pre-eclampsia, thrombotic thrombocytopenic purpura, typical and atypical hemolytic uremic syndrome, and hemolysis, elevated liver enzymes, low platelets syndrome and in non-pregnant patients with a wide differential diagnosis. The patient required 7 sessions of plasma exchange along with systemic steroids. During her illness, she developed rising liver enzymes and bilirubin, diffuse intravascular coagulation, renal failure, alveolar hemorrhage, and acute fulminant hepatic failure. A contrast-enhanced computed tomography scan revealed multiple areas of liver infarction with patent hepato-portal vessels. The patient required continuous renal replacement therapy and high supportive care. She stayed in the intensive care unit for 9 days, developed multi-organ failure, and finally expired. It is highly imperative to be aware of the complications of postpartum hemorrhage, as it should be treated promptly to minimize the possible cascade of multi-organ failure with high maternal and fetal mortality. Liver transplantation is the only possible radical therapy in cases with fulminant hepatic failure, worth considering, if clinically possible and applicable.